2017
DOI: 10.1038/s41398-017-0038-x
|View full text |Cite
|
Sign up to set email alerts
|

Lower cognitive control network connectivity in stroke participants with depressive features

Abstract: Around one-third of people develop depression following ischaemic stroke, yet the underlying mechanisms are poorly understood. Post-stroke depression has been linked to frontal infarcts, mainly lesions in the left dorsolateral prefrontal cortex (DLPFC). But depression is a network disorder that cannot be fully characterised through lesion-symptom mapping. Researchers of depression in non-stroke populations have successfully tapped into the cognitive control network (CCN) using the bilateral DLPFC as a seed, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 50 publications
0
37
0
2
Order By: Relevance
“…Additionally, both clinical and pre-clinical studies demonstrate the important role of reciprocal connections between the amygdala and PFC in the regulation of anxiety [25,40,42,43]. The MRI data from stroke patients provide supports that disruptions in thalamocortical and/or PFC pathways may contribute to the occurrence of PSD [44,45], and Vahid-Ansari F et al demonstrated stroke injuries in PFC led to the persistent anxiety/depression like phenotypes in lab mice [46]. In the present investigation of the focal cortical stroke model, the PFC was not a typical ischemic region and no significant cell death of TUNEL positive cells was observed in this region after stroke.…”
Section: Discussionmentioning
confidence: 85%
“…Additionally, both clinical and pre-clinical studies demonstrate the important role of reciprocal connections between the amygdala and PFC in the regulation of anxiety [25,40,42,43]. The MRI data from stroke patients provide supports that disruptions in thalamocortical and/or PFC pathways may contribute to the occurrence of PSD [44,45], and Vahid-Ansari F et al demonstrated stroke injuries in PFC led to the persistent anxiety/depression like phenotypes in lab mice [46]. In the present investigation of the focal cortical stroke model, the PFC was not a typical ischemic region and no significant cell death of TUNEL positive cells was observed in this region after stroke.…”
Section: Discussionmentioning
confidence: 85%
“…Moreover, depressive symptoms increase gradually after left dlPFC traumatic brain injury and stroke depending on the extent of damage and network impact . Indeed, large‐scale network effects, hemispheric asymmetries, and connectivity play an important role in the development of depressive symptoms (eg, post‐stroke depression has been linked to altered dlPFC functional connectivity) . Functionally, the left dlPFC might regulate negative affect via the frontoparietal cognitive control network .…”
Section: Discussionmentioning
confidence: 99%
“…Network dysfunctions such as reduce d DMN within-connectivity involving left middle temporal cortex and precuneus 35 and affective network 36 have been used to predict the severity of PSD symptoms. Egorova et al 37 reported that the network dysfunction related to depressive symptoms was not necessarily associated with network lesions. This result raised a hypothesis of brain plasticity in network recovery.…”
Section: Discussionmentioning
confidence: 99%